COVID-19 and Work–Family Conflicts in Germany: Risks and Chances Across Gender and Parenthood - Reimann, Mareike; Peters, Eileen; Diewald, Martin (Frontiers in Sociology, 2022)
The COVID-19 pandemic has dramatically affected everyone’s daily life in one way or another, requiring a re-negotiation of existing strategies for work–life integration, not only for individuals but also within families and partnerships. To contribute to existing knowledge on work-life integration during COVID-19 in Germany, we look at gender and parenthood differences in the experiences of work-to-family (WFC) and family-to-work (FWC) conflicts. By accounting for employees’ previous conflict experiences, we were able to reveal the extent to which the current conditions contributed to differences in these conflicts. Moreover, we explored the relevance of demands and resources in the family and work spheres as a way to explain different levels of WFC and FWC across gender and parenthood. Our analyses are based on a sample of 660 employees from a German linked employer–employee panel study and a COVID-19 follow-up survey conducted in late 2020. Results revealed that work–family conflict experiences before the pandemic play an important role in current conflict perceptions. Whereas WFC were more likely to be accentuated during the pandemic, prior FWC experiences may have helped to mitigate conflicts under these new conditions. Work–family conflicts in general have increased during the COVID-19 pandemic, but this finding applied only to conflicts in the family-to-work direction. Although such increases were not limited to parents, they were particularly high in this group. Overall, gender differences in work–family conflicts were absent, but differences were found between mothers and fathers. The need to compensate for a lack of external childcare, as well as having to work from home, increased FWC, especially among fathers. This study suggests that FWC in particular became more important during the pandemic; however, parents were not the only ones who were disadvantaged when it came to work–life integration; childless individuals likewise struggled to balance the demands of work and private life.